Pendidikan Life Skills dalam Penanaman Nilai-Nilai Agama Islam di Sekolah Dasar - Susandi , Ari (LPPPM STAI Darul Hikmah Bangkalan, 2020)
Life skills Education forms the pattern of a person or individual's relationship in the involvement of potential self and life skills both in the school and community environment, regulating the values ​​of Islamic education since the early days is still very much needed applying in the context of school discussions about social development for children, children, children, children, children, children, children, children, children, children, children, children, the purpose of the discussion of this article is with a qualitative descriptive analysis with literature review is life skills education is very helpful for educators in instilling the values ​​of the Islamic religion that is the value of discipline, honesty, responsibility and independence because life skill education is how the students can cope with and explore the potential that they discuss with the habits given by their educators so that students will le it is easy to accept the appropriate patterns and refractions that are corrected by educators and will bring a positive attitude to students' character. Keywords: educational life skills; Islamic religious values; primary school